The origins of town life in Ireland : spatial integration and urbanization in the kingdom of the Déisi, 700-1100 - Wall, Rebecca (Trinity College (Dublin, Ireland). Department of History, 2011)
This thesis investigates the origins of towns in pre-Norman Ireland by examining a case-study area in southeastern Ireland, the early medieval kingdom of the Déisi. Both documentary and archaeological sources are used to reconstruct and assess developments in secular and ecclesiastical politics, settlement patterns and economic organization in the Deisi kingdom between the eighth and the eleventh centuries. The fundamental assumption underlying this thesis is that the origins and development of towns are best studied in their regional context. This derives from the idea that town development or urbanization forms one strand of a wider trend toward increasing spatial integration, which has an impact not only on developing towns, but on places that remain rural throughout the period in question.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin